Fraud Prevention System with Whistleblowing System in Health Services: A Systematic Review - Ridwan, Ridwan; Munadi, Said; Fahlevi, Heru; Nadirsyah, Nadirsyah (Jurnal Jaminan Kesehatan Nasional, 2024)
The objective of this study is to ascertain the strategies employed in mitigating fraudulent activities within the realm of health services through the utilization of a whistleblowing mechanism. Methods: The present study employed a systematic review approach to examine relevant literature by utilizing specific keywords such as "whistleblowing system" and "fraud Healthcare." These keywords were then used to search for publications in the Scopus database, focusing on journals that mostly relied on secondary data. The search was conducted using the publish or perish tool. 8. Subsequently, a curation of scholarly publications and articles was conducted, employing a criterion centered on the thematic relevance of their titles. The selected publications have the objective of mitigating fraudulent activities within the healthcare industry and other interconnected industries that contribute to research endeavors. The findings of this study suggest that the implementation of a fraud reporting system is vital inside an organization, particularly within the context of health services. To enhance the caliber of healthcare services, internal healthcare staff and participants may report well, it is imperative to establish a system that ensures the preservation of reporter confidentiality, hence facilitating an increase in the volume of reports.